Additive binding layers to suppress free edge delamination in composite laminates under tension. (May 2022) - Ubago Torres, Miguel; Jalalvand, Meisam
Highlights: Free-edge delamination is successfully stopped. Additive thin-ply layers are placed at the free edges. Angle-ply laminates enhanced their mechanical properties by about 50%. Failure mechanisms not triggered by free-edges are not significantly affected. Abstract: An additive laminate applied to the free-edges of composite laminates is proposed to stop the development of delamination. Numerical analyses were conducted to find the optimum additive binding layup and the experimental results proved that the free-edge delamination was successfully suppressed. When it was used to bind the edges of a [ ( 20 2 / - 20 2 ) 2 ] s angle-ply laminate, the tensile failure strain and load of the laminate were increased by about 50%, and the failure mode changed from free-edge delamination to in-plane shear. However, it did not change the failure load and final failure mode of a [ 45 2 / 0 2 / - 45 2 / 90 2 ] s quasi-isotropic laminate, as this substrate is less susceptible to free-edge delamination. Thus, this technique is an efficient solution for suppressing free-edge delamination in real structural applications and in the characterisation of coupon tests where damage at the free-edges undermines the real potential of the composite substrate.